2016
DOI: 10.1038/srep36394
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 inhibitor rapamycin and ER stressor tunicamycin induce differential patterns of ER-mitochondria coupling

Abstract: Efficient mitochondrial Ca2+ uptake takes place at contact points between the ER and mitochondria, and represents a key regulator of many cell functions. In a previous study with HeLa cells, we showed that ER-to-mitochondria Ca2+ transfer increases during the early phase of ER stress induced by tunicamycin as an adaptive response to stimulate mitochondrial bioenergetics. It remains unknown whether other types of stress signals trigger similar responses. Here we observed that rapamycin, which inhibits the nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 47 publications
4
38
0
Order By: Relevance
“…Recent reports show that ER stress can positively regulate ER-mitochondria communication in HeLa cells 55 , 56 . In our experimental system, acute ER stress promoted a clear disruption of ER-mitochondria communication, and its AKT-mTOR-dependent re-establishment clearly correlated with the dynamics of UPR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports show that ER stress can positively regulate ER-mitochondria communication in HeLa cells 55 , 56 . In our experimental system, acute ER stress promoted a clear disruption of ER-mitochondria communication, and its AKT-mTOR-dependent re-establishment clearly correlated with the dynamics of UPR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Bravo-Sagua and coworkers [63] showed that ER stress, during its early stage, increases the ER-mitochondria contacts, thus leading to an adaptive increase in mitochondrial energetics. This appears to be a generic response to acute stress, as we similarly observed such changes upon inhibition of the nutrient-sensing kinase mammalian target of rapamycin complex 1 (mTORC1) [80]. In fact, RM enables lysate treated cells to maintain a high mitochondrial membrane potential, accordingly to the decrease of the apoptotic process.…”
Section: Discussionmentioning
confidence: 60%
“…ER stress induced by thapsigargin in human cancer cells 67 or tunicamycin in HeLa cells 68 promoted cell death involving mitochondrial swelling, dissipation of the electrochemical gradient and opening of the mPTP. However, in HT22 cells ER stress induced by brefeldin A, thapsigargin or tunicamycin induced caspase-dependent cell death through enhanced ER-Ca 2+ release that was independent of mitochondrial damage.…”
Section: Discussionmentioning
confidence: 99%